Mipham's Sword of Wisdom: The Nyingma Approach to Valid Cognition - Dpalldan-Sherab, Rinpoche (Wisdom, 2018)
Presents the Nyingma-lineage understanding of valid cognition in Buddhism. Its core subject is the Buddhist view of the two truthsthe relative truth of conventional appearances and the absolute truth of emptiness and buddha natureand how the two truths are inseparable. The main questions posed are: How can we know the two truths and how can we be certain that our knowledge is accurate?